EFEKTIVITAS PEMBUATAN PERATURAN DAERAH KHUSUS DI PROVINSI PAPUA: STUDI MAJELIS RAKYAT PAPUA - Hamjah Bonso; Herman Lawelai (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Buton, 2020)
Abstract: The presence of the special autonomy law in Papua has had an impact on institutions. This can be seen with the formation of the Papua People's Assembly (MRP). This study aims to determine the effectiveness of making specific regional regulations in the province of Papua. This study uses a